Synthesis of new two‐dimensional titanium carbonitride Ti2C0.5N0.5Tx MXene and its performance as an electrode material for sodium‐ion battery. Issue 12 (12th December 2021) - Liang, Kun; Tabassum, Anika; Majed, Ahmad; Dun, Chaochao; Yang, Feipeng; Guo, Jinghua; Prenger, Kaitlyn; Urban, Jeffrey J.; Naguib, Michael
Abstract: Two‐dimensional (2D) layered transition metal carbides/nitrides, called MXenes, are attractive alternative electrode materials for electrochemical energy storage. Owing to their metallic electrical conductivity and low ion diffusion barrier, MXenes are promising anode materials for sodium‐ion batteries (SIBs). Herein, we report on a new 2D carbonitride MXene, viz ., Ti2 C0.5 N0.5 T x (T x stands for surface terminations), and the only second carbonitride after Ti3 CNT x so far. A new type of in situ HF (HCl/KF) etching condition was employed to synthesize multilayer Ti2 C0.5 N0.5 T x powders from Ti2 AlC0.5 N0.5 . Spontaneous intercalation of tetramethylammonium followed by sonication in water allowed for large‐scale delamination of this new titanium carbonitride into 2D sheets. Multilayer Ti2 C0.5 N0.5 T x powders showed higher specific capacities and larger electroactive surface area than those of Ti2 CT x powders. Multilayer Ti2 C0.5 N0.5 T x powders show a specific capacity of 182 mAh g −1 at 20 mA g −1, the highest among all reported MXene electrodes as SIBs with excellent cycling stability. Abstract : Synthesis of new two‐dimensional titanium carbonitride Ti2 C0.5 N0.5 T x MXene and its performance as an electrode material for sodium‐ion battery